Comparative study of efficacy and safety of intravenous ferric carboxymaltose versus iron sucrose in treatment of post-partum anemia - T., Jayanthy; Asranna, Apoorva; Raman, Ragvi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Ferric carboxymaltose has been recently introduced for the treatment of anaemia. The present study was planned to compare the efficacy, tolerability and safety of intravenous ferric carboxymaltose with intravenous iron sucrose in the treatment of iron deficiency anaemia among postpartum women. Methods: A total of 60 postpartum women with haemoglobin levels between 7-10 g/dl were randomized into two groups: 30 in group A (received iron carboxymaltose) and 30 in group B (Received iron sucrose). Haemoglobin and serum ferritin levels were done on day 0 and after 6 weeks. Results: The post treatment haemoglobin levels were found to be 10-10.9 g/dl in 66.7% of women in group A and 63.3% in group B. The mean post treatment haemoglobin levels in group A was 9.97±0.3 g/dl and in group B was 10.9 g/dl (p<0.001). The mean increase in haemoglobin levels post treatment were significantly high in group B (2.1±0.5 gm%) compared to group A (1.3±0.5 gm%). The mean post treatment S. Ferritin levels in group A was 91.2±25.8 and in group B was 126.5±23.2 gm%. The mean increase in S. Ferritin levels post treatment were significantly high in group B (96.9±23.3) compared to group A (62.7±22.6) (p<0.001). Conclusions: Intravenous iron carboxymaltose is more effective and better tolerated in the treatment of iron deficiency anaemia among postpartum women compared to intravenous iron sucrose.